The Effect of Current Ratio and Account Receivable Turnover on Return On Assets in Food and Beverage Companies Listed on the Indonesia Stock Exchange for the 2019-2021 Period - Nia Apriyani Pinem (Jurnal Ekonomi Bisnis Digital, 2023)
This study aims to determine whether "The Effect of Current Ratio and Account Receivable Turnover on Return On Assets in Food and Beverage Companies Listed on the Indonesian Stock Exchange for the 2019-2021 Period". The research design used in this study is an associative method with a quantitative approach. The population in this study is that there are 21 companies that are included in the Food and Beverage company sub-sector for the 2019-2021 period. The sample in this study was 13 companies which over a period of 3 years totaled 39 samples to be used in this study. The results of this study indicate that the Current Ratio partially has a significant effect on Return On Assets. Receivable Account Turnover partially has a significant effect on Return On Assets. Current Ratio and Account Receivable Turnover simultaneously have a significant effect on the dependent variable (Return On Assets).